2020
DOI: 10.5787/47-1-1270
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Work Satisfaction of Single Parents in the South African National Defence Force: An Exploratory Study

Abstract: There has been a documented increase in single-parent families over the years. Various causes, such as divorce, death, irresponsible fathers and choice, to mention but a few, contribute to this increase. Since 2005, the South African National Defence Force (SANDF) has been partaking in various peacekeeping missions on the continent. The deployment of the SANDF is, however, not limited to cross-border activities. The SANDF also deploys its soldiers within the country in border control operations. While some sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 161 publications
0
2
0
Order By: Relevance
“…As this burden is out of the family's control, it increases the stress levels in the household. Matjeke (2017:3) mentions that the SANDF previously deployed soldiers outside the borders of South Africa for a period of 6 months or less. Currently, the deployment period is 12 months, with a possible 2 weeks of leave in between.…”
Section: Introductionmentioning
confidence: 99%
“…As this burden is out of the family's control, it increases the stress levels in the household. Matjeke (2017:3) mentions that the SANDF previously deployed soldiers outside the borders of South Africa for a period of 6 months or less. Currently, the deployment period is 12 months, with a possible 2 weeks of leave in between.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in this field showed that single parents experience lower satisfaction with their life-course, and satisfaction with the future. Further, single parents might experience high levels of work-family conflict which can have negative effects on their job satisfaction (Burden, 1986;Matjeke, 2016). However, their level of satisfaction with health (Herbst, 2012) and satisfaction with their financial situation (Medgyesi & Zólyomi, 2016) do not differ significantly from the rest of the population.…”
Section: Life Events and Domain-specific Subjective Well-beingmentioning
confidence: 99%